FUNCTIONAL-SEMANTIC GAMES OF MICROTEXTS CHARACTERISTIC OF JOURNALISTIC STYLE (Scientific journal of the Fergana State University, 2024)
This article is dedicated to the systematic study of the functional characteristics of journalistic style microtexts that reflect the complex and current socio-political issues of our time, aspects that differ from other style texts, and the semantic relations that create the functionalization of microtexts. the specific functions of relationships in increasing the visuality, believability, and effectiveness of the text are analyzed by means of linguistic evidence.